THU0600 High vaccine coverage rates are not enough: vaccination delay and risk for vaccine- preventable diseases in paediatric patients with rheumatic diseases with and without immunosuppressive therapy. (12th June 2018) - Welzel, T.; Zumbrunn, T.; Bonhoeffer, J.; Cannizzaro Schneider, E.; Hofer, M.; Kaiser, D.; Hentgen, V.; Woerner, A.
Abstract : Background: Paediatric patients with rheumatic diseases (PedRD) are more susceptible to invasive infectious diseases, due to their underlying disease, high disease activity and immunosuppressive therapy (IT). 1, 2 In Switzerland, specially indicated (SI) vaccinations for PedRD patients against pneumococcus, varicella zoster, hepatitis B, influenza and human papilloma virus should be administered as early as possible. On-time and complete coverage reduces the risk of vaccine-preventable infections 3 and its associated morbidity. Information about on-time vaccination is scarce, especially in PedRD patients. Objectives: To assess the relationship of vaccine coverage and on-time vaccination in PedRD patients in Switzerland with and without IT. Methods: Multicenter retrospective prevalence study based on the Juvenile Inflammatory Rheumatism (JIR) cohort, an international registry for rheumatic diseases. Patients treated in Swiss paediatric rheumatology centres (Basel, Geneva, Lausanne, Lucerne, Zurich) were included. Vaccine coverage and timeliness of administered vaccines were assessed for routine and for SI vaccinations according to the Swiss Federal Office of Public Health. Results: 239 patients were included. 93 (39%) received IT during a median observation period of 2.7 years (IQR 1.1–5.4). Median age was 6.7 years (IQR 2.9–10.3) at diagnosis, 10.9 years (IQR 7–14.3) at reference date (12th April 2016). At diagnosis, 185 patients (77%) had complete routine vaccine coverage; 76 (32%) fulfilled Swiss on-time immunisation criteria. At reference date, the routine vaccine coverage rate decreased to 74% with on-time vaccination achieved in 29% of PedRD patients without IT and in 23% with IT, respectively. Completeness of SI vaccinations was documented in 19 PedRD patients (13%) without IT and 6 patients (6.5%) with IT. On-time vaccination for SI vaccination was fulfilled in 7 patients without IT; no patient with IT was vaccinated on-time. Only 23 (9.6%) patients showed complete and thereof 4 (1.6%) on-time vaccination status for routine and SI vaccinations. Conclusions: Despite moderate to high routine vaccination coverage in Switzerland, vaccinations particularly recommended for PedRD patients to prevent from complications, are incompletely administered. Moreover, the high frequency of delayed vaccination implicates a potential increase of vaccine-preventable disease. Close surveillance of vaccination status improves standard of care for this susceptible population. References: [1] Becker I, Horneff G. Risk of Serious Infection in Juvenile Idiopathic Arthritis Patients Associated With Tumor Necrosis Factor Inhibitors and Disease Activity in the German Biologics in Pediatric Rheumatology Registry. Arthritis Care Res (Hoboken)2017Apr. 69(4):552–560. [2] Brunelli JB, Schmidt AR, et al. High rate of serious infection in juvenile idiopathic arthritis patients under biologic therapy in a real-life setting. Mod Rheumatol2017Sep;1-7. [3] Crawford NW, Bines JE, et al. Optimizing immunization in pediatric special risk groups. Expert Rev Vaccines2011Feb;10(2):175–86. Disclosure of Interest: T. Welzel: None declared, T. Zumbrunn: None declared, J. Bonhoeffer: None declared, E. Cannizzaro Schneider: None declared, M. Hofer Grant/research support from: AbbVie, Novartis, Consultant for: Novartis, D. Kaiser: None declared, V. Hentgen: None declared, A. Woerner: None declared